Analisis Kinerja Simpang Non-APILL (Studi Kasus: Simpang Jalan Pulau Galang – Jalan Taman Pancing – Jalan Tukad Baru) - Ni Putu Delima Yogeswari Saraswati; P. Kwintaryana; Putu Budiarnaya; Rudolfo Xavier Lobato Gusmao (Universitas Pendidikan Nasional, 2022)
Population growth in Denpasar City continues to increase from year to year. This indirectly causes the number of vehicle ownership in Denpasar City to continue to increase while the existing facilities are inadequate. We can see this in traffic problems such as congestion that often occurs, especially at intersections. Jalan Pulau Galang - Jalan Taman Pancing - Jalan Tukad Baru is an example of an intersection that has irregular traffic conflict points, especially during rush hours. This junction is a non APILL junction. This location was chosen as the research because in addition to the irregular traffic flow at certain hours, at this intersection there are also residential and shopping areas which trigger more congestion at this intersection. From the problems that arise at the Jalan Pulau Galang intersection - Jalan Taman Pancing - Jalan Tukad Baru, a study was carried out which aims to determine the performance and service level of the intersection. If the service level at the intersection is in the safe category, then preventive measures to avoid congestion must be analyzed. The results of the calculations that have been carried out show that the value for the intersection capacity (C) is 6,213 smp/jam with the degree of saturation (DS) being 0,363 smp/jam. The DS (Degree of Saturation) value indicates that the intersection is included in the service level category B according to the 2014 PKJI, which has stable flow characteristics, but the operating speed is starting to be limited by traffic conditions. Service level B has an NVK value between 0.20-0.44. For this reason, it is necessary to supervise the location of the intersection so that the location of the intersection still has an adequate level of service and does not increase in height to avoid severe traffic jam